Description of the immature stages of Froeschneria piligera (Stål) (Hemiptera: Heteroptera: Lygaeoidea: Rhyparochromidae: Myodochini), its distribution in Mexico and notes on its biology - Cervantes Peredo, Luis; Briceño Báez, Marcela (Instituto de Ecología, A.C., 2010)
Descriptions and illustrations of all instars about Froeschneria piligera (Stål), and notes on its biology, it has been found feeing on the seeds of several plants, mainly species of Asteraceae, it is also considered a facultative terrestrial species, because it feeds on some species of Ficus. It was reared in the laboratory using sunflower seeds.